Ethnic Disparities in Thrombotic and Bleeding Diatheses Revisited: A Systematic Review of Microsurgical Breast Reconstruction across the East and West - Bene, Nicholas C.; Minasian, Raquel A.; Khan, Saiqa I.; Desjardins, Haley E.; Guo, Lifei (Journal of Reconstructive Microsurgery, 2021)
Background Ethnicity has been shown to play a role in disparate coagulative responses between East Asian and Caucasian patients undergoing nonmicrovascular surgery. In this study, we sought to further investigate this hematologic phenomenon between the two ethnic groups within the field of microsurgical breast reconstruction.Methods A systematic review examining the reported incidence of microvascular thrombosis and all-site bleeding among breast free flaps in East Asians and Westerners was performed. Statistical analysis was performed using the chi-square test.Results Ten East Asian studies with 581 flaps and 99 Western studies with 30,767 flaps were included. A statistically significant higher rate of thrombotic complications was found in Westerners compared with East Asians (4.2 vs. 2.2%, p = 0.02). Conversely, bleeding events were more common in East Asians compared with Westerners (2.6 vs. 1.2%, p = 0.002).Conclusion There appears to be an ethnicity-based propensity for thrombosis in Westerners and, conversely, for bleeding in East Asians, as evident by the current systematic review of microvascular breast reconstruction data. It is therefore advisable to consider ethnicity in the comprehensive evaluation of patients undergoing microsurgical procedures.
Keywords: ethnicity; breast; microsurgery; coagulation